Analisis Ragam Bahasa Jepang Berdasarkan Konsep Uchi-soto dalam Drama Hanzawa Naoki - Fitriana, Melinia Nur; Wardhana, Chevy Kusumah; Setiawati, Ai Sumirah; Diner, Lispridona; Nurhayati, Silvia (Program Studi Sastra Jepang, Universitas Jenderal Soedirman, 2024)
Japanese people in interacting tend to place themselves in social groups (uchi-soto). This study discusses the variety of Japanese speech based on the concept of uchi-soto in the Hanzawa Naoki drama. The main setting of the drama which is the work environment makes the concept of uchi-soto greatly affect the characters in communicating. The importance of learning the concept of uchi-soto will arise when there are misunderstandings due to lack of understanding when interacting with Japanese people. The results of this study are expected to be used by students as a reference for the variety of Japanese language with the uchi-soto concept so that they can apply it in real life according to the situation so as not to cause misunderstandings when communicating between speakers and interlocutors. This study aims to determine the variety of Japanese speech based on the concept of uchi-soto in Hanzawa Naoki's drama and to find out the factors behind the use of speech variety based on the concept of uchi and soto.